The role of lecturer in enhancing collaborative learning among students through e-learning at Faculty of Education,University of Technology Malaysia (UTM) - Ali, Mohd. Fadzli (2006)
E-learning has been utilised widely in the teaching and learning process in many institutions of higher learning in Malaysia, including University Technology Malaysia (UTM). UTM has chosen the user-friendly Learning Management System (LMS) called Moodle™ as a platform to conduct the teaching and learning process through e-learning. Through its forum facility, interactions and collaborations among lecturers and students can take place. However, the effectiveness of implementing collaborative e-learning highly depends on the role of the lecturers themselves. This study looks at the role of lecturers in enhancing students’ learning through collaborative e-learning at the Educational Multimedia Department, Faculty of Education, UTM. The respondents of this study are 10 lecturers from the Educational Multimedia Department. A survey method is selected for the study and questionnaires are distributed to the responents to collect the data needed. All the data are processed to obtain the result in mean and percentage. The researchers focus on three main aspects which include (i) lecturers’ skills in managing the e-learning system; (ii) lecturers’ skills in delivering their courses through e-learning; (iii) participations between the lecturers and the students in e-forum facilities.